Social Media Crisis Communication Strategies: Lessons Learned from the Naira Marley and Mohbad Controversy - Oluwatoyosi, Ajayi David (Journal of Information and Knowledge, 2025)
This study investigates crisis communication practices within the music industry, focusing on music labels and artists. Through a mixed-methods approach combining quantitative surveys and qualitative interviews, the study explores the role of social media, the effectiveness of crisis communication strategies, and best practices for managing crises. Findings reveal that proactive strategies, transparency, and authenticity are crucial for maintaining brand image and public trust during crises. Social media emerges as a powerful communication channel, but its strategic utilisation is essential to mitigate negative impacts. The study emphasises the importance of comprehensive crisis communication plans, social media monitoring, transparency, authenticity, and regular training for stakeholders. These recommendations provide valuable insights for music labels and artists to enhance their crisis communication readiness and resilience in the dynamic music industry landscape. Further research is needed to explore evolving challenges and emerging best practices in crisis communication within the music industry.